Tempeh as an alternative protein source in the diets for tiger grouper, Epinephelus fuscoguttatus juvenile - Chor, Wei Kang (2015)
Tiger grouper (TG, Epinephelus fuscoguttaus) is among the most commonly cultured grouper species in Asia Pacific region due to high demand and good performance in captivity. However, the fish production is challenged by the high production cost mainly due to the heavy reliance on fish-based feed. Previous study on fish meal (FM) replacement with soybean meal (SBM) reported that at least 30% of the FM protein can be replaced by SBM with supplementation of phytase in the diet of tiger grouper. Tempeh (TMP), another type of processed (fermented) soy product was commonly reported to contain fewer antinutrients, more nutritious and easier to digest for human. It is expected that higher inclusion of soy product in the diet of TG is possible by using TMP with the supplementation of essential amino acids (EAAs) and feeding stimulant (FS). Therefore, in the present study, two experiments were carried out to evaluate 1) the potential of locally available fermented soybean, TMP as an alternative protein source and 2) the effects of EAAs and FS supplementation in TMP-based diets on TG. In Experiment 1, five dietary treatments of isoproteic (50%) and isolipidic (12%) diets were formulated to replace FM with TMP at 0, 30, 40, 50% (namely T0, T30, T40, and T50, respectively), and with SBM at 30% replacement level with phytase (S30) and fed to triplicate groups of juvenile TG (10.09±0.15g) for 56-days. Distal intestine (DI) and feces of experimental fish were sampled after feeding trial for histological observation and determination of apparent digestibility coefficient (ADC) of nutrients, respectively. Fish fed with T0 attained the highest weight gain (WG) and feed intake (FI), followed by S30 than other TMP-based diets (P< 0.05). Among all groups fed with TMP-based diets, T40 attained the highest WG (165.55%) but the FI decreased significantly with the increased level on TMP in the diets (P< 0.05). Despite the poorer WG and FI, T40 and T50 groups resulted in better feed conversion ratio (FCR), protein efficiency ratio (PER) and net protein utilization (NPU) (P< 0.05) than other diets. In general, fish fed with all dietary treatments showed relatively high dry matter, crude protein and crude lipid apparent ADCs (ranging 81.78-89.87%, 93.07-94.71% and 91.01-99.17%, respectively) except for fish fed T50 in which resulted in poor lipid ADC (78.22%). Interestingly, reduced SBM-induced enteritis occurrence was observed in those fed with T30 compared to S30. In Experiment 2, another 56-day feeding trial was carried out to evaluate the effects of EAAs and FS (predetermined mixture of crystalline amino acids for grouper) supplementation in the diets using T40 as basal diet. T0, T40, T40 supplemented with EAAs (T40AA), T40 supplemented with FS (T40FS), and T40 supplemented with both EAAs and FS (T40MIX) were fed to triplicate of fish (22.93±0.50g) close to apparent satiation. Significantly higher WG were observed in T0 group (144.31%) than the rest of the diets (P< 0.05). Among TMP-based diets, better WG and FI were observed in those fed T40MIX with both FS and EAAs supplementation (100.1% and 0.65 g fish-1 day-1) than T40AA and T40FS (P< 0.05). Histological observation on DI showed that supplementation of either EAAs or FS has the potential to reduce SBM-induced enteritis. In conclusion, the utilization of TMP-based diets can be improved by the supplementation of both EAAs and FS supplementation. The full potential of TMP as an alternative protein source can be further explored by appropriate supplementation level of EAAs and FS in the diet.